Implementasi Rancangan Pembelajaran Berbasis Sharing dan Jumping Task pada Konsep Hukum Kekekalan Massa - Etrie Jayanti (Orbital: Jurnal Pendidikan Kimia, 2021)
The law of conservation of mass is a fundamental law and is related to other chemical materials such as chemical reaction equations so that student's learning obstacles of the law of conservation of mass must be overcome. One of the ways to overcome student's learning obstacles of the law of conservation of mass concept is the implementation of sharing and jumping task based lesson design, which is the aim of this research. The research method used is a qualitative descriptive research method. The research subjects were students of X.1 and X.2 SMA in Bandung and chemistry teacher who collaborate with researcher as team teaching. The data on the implementation of sharing and jumping task based lesson design of the law of conservation of mass was obtained from observations, tests, and interviews. Implementation of sharing and jumping task based lesson design of the law of conservation of mass concept was carried out twice. The result of the first implementation is that the previously identified learning obstacles still appear but in a smaller percentage. After the first implementation of the lesson design, it was revised and implemented in other class. The results of the second implementation can overcome student's learning obstacle who think that the mass of solids is heavier than the mass of liquids, but a small number of students still do not take into account the mass of gases in chemical reactions and do not fully understand the meaning of the law of conservation of mass.